2G HTS wires made on 30 μm thick Hastelloy substrate. (15th September 2016) - Sundaram, A; Zhang, Y; Knoll, A R; Abraimov, D; Brownsey, P; Kasahara, M; Carota, G M; Nakasaki, R; Cameron, J B; Schwab, G; Hope, L V; Schmidt, R M; et al.
Abstract: REBCO (RE = rare earth) based high temperature superconducting (HTS) wires are now being utilized for the development of electric and electromagnetic devices for various industrial, scientific and medical applications. In the last several years, the increasing efforts in using the so-called second generation (2G) HTS wires for some of the applications require a further increase in their engineering current density ( J e ). The applications are those typically related to high magnetic fields where the higher J e of a REBCO wire, in addition to its higher irreversibility fields and higher mechanical strength, is already a major advantage over other superconducting wires. An effective way to increase the J e is to decrease the total thickness of a wire, for which using a thinner substrate becomes an obvious and attractive approach. By using our IBAD-MOCVD (ion beam assisted deposition-metal organic chemical vapor deposition) technology we have successfully made 2G HTS wires using a Hastelloy ® C276 substrate that is only 30 μ m in thickness. By using this thinner substrate instead of the typical 50 μ m thick substrate and with a same critical current ( I c ), the J e of a wire can be increased by 30% to 45% depending on the copper stabilizer thickness. In this paper, we report the fabrication and characterization of the 2G HTS wires made on the 30 μ m thick Hastelloy ® C276 substrate. It was shown that with the optimization in the processing protocol, the surface of the thinner Hastelloy ® C276 substrate can be readily electropolished to the quality needed for the deposition of the buffer stack. Same in the architecture as that on the standard 50 μ m thick substrate, the buffer stack made on the 30 μ m thick substrate showed an in-plane texture with a Δ ϕ of around 6.7° in the LaMnO3 cap layer. Low-temperature in-field transport measurement results suggest that the wires on the thinner substrate had achieved equivalent superconducting performance, most importantly the I c, as those on the 50 μ m thick substrate. It is expected the 2G HTS wires made on the 30 μ m thick Hastelloy ® C276 substrate, the thinnest and with the highest J e to date, will greatly benefit such applications as high field magnets and high current cables.